Performance analysis of DECK collective communication service - Silva, R.; Picinin, D.; Barreto, M.; Avila, R.; Diverio, T.; Navaux, P. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2003: Anais do XV Symposium on Computer Architecture and High Performance Computing, 2003)
Collective communication is very useful for parallel applications, especially those in which matrix and vector data structures need to be manipulated by a group of processes. We present a performance analysis of collective communication primitives designed for the DECK parallel programming environment, with the aid of different numerical methods used to solve hydrodynamics and mass transportation models.